THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN MANAGING PROFESSIONAL SPORTS CLUBS - Badaruddin, Badaruddin (Penelitian dan Pengembangan Ilmu, 2025)
The professional sports industry faces high competitive and operational pressures, including performance demands, fan loyalty, sponsorship expectations, and media scrutiny. Human resource (HRM) management plays a strategic role in determining the success of professional sports clubs, yet the application of transformational leadership (TL) in this context remains limited, particularly regarding the mechanism of its influence on club performance through HRM practices.This research uses an approach/narrative review, with literature analysis from Scopus, Web of Science, and ProQuest databases (2010–2025), using keywords such as “transformational leadership,” “sports management,” and “human resource management.” The literature was analyzed based on the dimensions of TL, HRM practices, and club performance outcomes, while identifying patterns, gaps, and mediating mechanisms of HRM.The results show that the TL dimensionidealized influence, inspirational motivation, intellectual stimulation, And individualized consideration encourage motivation, job satisfaction, talent retention, and innovation for staff and athletes. Effective HRM practices, such as adaptive training, coaching, and performance management, serve as key mediators who translate the influence of TL into improved team and overall organizational performance.Effective integration of TL and HRM practices is essential for superior performance and sustainable success of professional sports clubs, and provides practical implications for managers and coaches.